Analysis of selected cytokines, NLRP3 inflammasome and α-Klotho protein in patients with heart failure after ICD/CRT-D high-voltage intervention - Szyller, Jakub; Śliwińska-Mossoń, Mariola; Hrymniak, Bruno; Olejnik, Agnieszka; Kozera, Łukasz; Zieliński, Maciej; Banasiak, Waldemar; Bil-Lula, Iwona; Jagielski, Dariusz (Frontiers in Physiology, 2026)
ObjectivesInflammatory cytokines contribute to Implantable Cardioverter-Defibrillator/Cardiac Resynchronization Therapy with a Defibrillator (ICD/CRT-D) high-voltage intervention by promoting arrhythmias through direct cardiac effects and indirect systemic changes. The NLRP3 inflammasome can promotes arrhythmias by linking inflammation, oxidative stress, and structural changes. The aim of this study was to assess the inflammatory response in the peri-shock-period in patients with heart failure (HF) and implanted ICD/CRT-D and the initial analysis of the possible role of cytokines, NLRP3 and soluble Klotho protein in peri-shock period and the possibility of triggering arrhythmias.MethodsThe study population consisted of 50 patients with diagnosed HF and implanted ICD/CRT-D devices. Blood samples were drawn up to max. 6 h after appropriate ICD/CRT-D intervention (“intervention group”) or from patients qualified for ICD/CRT-D device replacement (ERI status) and with no intervention min in the previous 3 months (“control group”). Serum concentration of TNF-α, IL-1β, IL-6, IL-10, IL-17, NLRP3 inflammasome, soluble Klotho protein and FGF-23 complete blood count, were determined in all individuals.ResultsIL-6 and IL-10 were higher after ICD/CRT-D appropriate intervention (3.3 pg/mL, 95% CI: 2.7–3.7 vs. 4.6 pg/mL, 95% CI: 2.9–14.5, p = 0.0399 and mean 7.8 pg/mL, 95% CI: 7.1–8.5 vs. 9.0 pg/mL, 95% CI: 8.1–9.9, p = 0.0321, respectively). The group was characterized by a higher number of white blood cells (WBC, 6.8 × 103/µL, 95% CI: 6.0–7.6 vs. 9.4 × 103/µL, 95% CI: 8.1–10.7, p = 0.0017), neutrophils (NEUTs, 4.1 × 103/µL, 95% CI: 3.4–4.8 vs. 6.5 × 103/µL, 95% CI: 5.3–7.7, p = 0.0007) and lower number of eosinophils (EOSs, 0.11 × 103/µL, 95% CI: 0.10–0.16 vs. 0.03 × 103/µL, 95% CI: 0.01–0.08, p = 0.0013). Serum concentration of soluble Klotho protein was significantly higher after device intervention (557.5 pg/mL, 95% CI: 495.5–619.5 vs. 895.2 pg/mL, 95% CI: 744.7–1,046.0, p < 0.0001), with no change in FGF-23 levels.ConclusionIn the peri-shock period, increased IL-6 and IL-10 serum concentrations and changes in 5-diff blood count (increased neutrophils and decreased eosinophils) are observed, which may be associated with a higher risk of ventricular arrhythmia in HF patients. A significant increase in α-Klotho protein concentration, should be taken into account in the development of future diagnostic methods and indicates an important protective role in the inflammatory process.